قانون رقم 211 لسنة 2020 بتعديل قانون الاجراءات الضريبة الموحدة = Law No. 211 of the year 2020 Amending The Uniform Tax Procedure Law - مصر (2025)
Law no. 211 of the year 2020 amending certain provisions of the uniform tax procedure law promulgated by law no. 206 of the year 2020 قانون رقم 211 لسنة 2020 بتعديل بعض أحكام الإجراءات الضريبية الموحد الصادر بالقانون رقم 206 لسنة 2020